A study of Impact of Rashtriya Bal Swasthya Karyakaram on Economic empowerment of Women in Mandsaur, M.P - Shukla, Abhikrati; Khimesara, Gyanchand (Gyan Management Journal, 2018)
In recent time "empowerment" is become one of the most widely used development terms especially in term of women. Still it is one of the least understood in terms of how it is measured or observed. Women Empowerment means to increase the, spiritual, political, social or economic strength of women among the societies and the communities to develop the confidence and their own capacity. Economic empowerment of women promotes women’s ability to achieve their rights and well-being while also reducing household poverty, increasing economic growth and productivity, and increasing efficiency. Rashtriya Bal Swasthya Karyakram (RBSK) aims at early identification and intervention for children from birth to 18 years to cover 4 ’D’s viz. Defects at birth, Diseases, Deficiencies, Development delays including disability. The study analyzes impact of Rashtriya Bal Swasthya Karyakaram on economic empowerment of women in Mandsaur district, M.P. The study aims to analyze the contribution of scheme towards women’s economic empowerment. It also assess the satisfaction among the women about the scheme based on its coverage and a/location of funds.